Examining Space Efficiency in Supertall Towers through an Analysis of 135 Case Studies - Ilgın, Hüseyin Emre (International Journal of Architectural Engineering Technology, 2023)
This study addresses the critical need for a comprehensive exploration of space efficiency in supertall buildings, a crucial aspect of skyscraper architecture with profound implications for sustainability. Despite the paramount importance of spatial utilization, the existing literature lacks a thorough investigation into this domain. This research aims to fill this significant gap by conducting an exhaustive analysis based on data from 135 case studies. The proposed model for evaluating space efficiency yielded compelling technical insights. The key metrics employed in this examination include: (1) average space efficiency: the findings revealed an average space efficiency of about 72%. This metric provides a quantitative measure of how effectively space is utilized in supertall buildings. (2) core area proportion: on average, the proportion of core area to the gross floor area was around 24%. This metric sheds light on the distribution of core areas within the overall structure, impacting both functionality and spatial optimization. This study also highlighted notable trends and characteristics observed in the examined cases: (3) central core design: the majority of skyscrapers featured a central core design tailored primarily for mixed-use purposes. This architectural choice reflects a strategic approach to maximize functionality and versatility in supertall structures. (4) structural systems: The outriggered frame system emerged as the prevailing structural system, with composite materials commonly used for the structural components. This insight into prevalent structural choices contributes to the understanding of the technical aspects influencing space utilization in skyscraper design.